Metodologia para cálculo de perdas técnicas e não técnicas de alimentadores de distribuição via estudos de fluxo de carga pelo Método Somatório de Potência Modificado - OLIVEIRA, Rafael Cavalcante de (Universidade Federal do Pará, 2017)
Fundamental to economic activity the electric energy sector in Brazil is regulated by the relevant agency, ANEEL. Which regulates and supervises the production, transmission / distribution and commercialization of electric energy in accordance with the policies of the federal government. Among other functions, ANEEL defines the tariff values to be charged by the concessionaires through tools such as Tariff Reviews. The non-technical losses (or commercial losses) of the electric power company are part of the energy tariff composition, being passed on to the final consumer, within a pre-established limit. Therefore reducing commercial losses is a fundamental issue for energy distributors, as it increases the profitability of the company and decreases energy costs to the end user. This work, being the result of a research project carried out in partnership between the power distribution utility of the state of Pará, CELPA, and the Federal University of Pará, UFPA, aims to develop a new methodology in the scope of operational planning, including technical loss information and techniques in load flow studies using modified Power Summation Method. Initially, an analysis of the scenario of the Brazilian electric sector is presented, with emphasis on the frauds and thefts of energy, considering the impacts of this reality from the financial point of view for both the energy concessionaires and the clients, as well as the impacts on the services to these consumers. Afterwards a new methodology, able to more assertively determine the actual operating state of the distribution network is showed, taking into account the commercial losses of energy, together with real measurements of active and reactive power injected in the feeders, in the point of common coupling with the substation. The method developed using both an IEEE 13-bus test feeder and an urban feeder of the Belém metropolitan network belonging to the Pará power utility CELPA, is applied and the results obtained are then presented and analyzed.